The Vanishing Siberian Crane - Sharma, V. D.; Sharma, Sunayan (Indian Forester, 1991)
The population of Siberian Crane (Grus leucogranus) a winter migrant to India is decreasing day by day. Studies have been conducted in the Keoladeo National Park from 1974 to 1991 about number of their coming, feed habit and breeding etc. Valuable information about their movements have also been recorded to provide authentic information about their speed.